Gender in Peru : Can Women be Integrated into Transport Projects? - Caballero, Luz (World Bank, Washington, DC, 2012)
The main achievement of the Rural Roads Project with regard to gender issues was the improvement of the bridle paths. This was not simply a result of female representation on the Rural Road Committees, which were the road rehabilitation crews, but also because during the participatory process of prioritizing roads to be improved, women, being the most frequent users of this type of road, enthusiastically expressed themselves and described how the lack of accessibility and transport services had impeded them in their daily lives. In addition, their basic needs were taken into consideration.